Pengaruh Kompetensi, Kompensasi, dan Lingkungan Kerja terhadap Kinerja Karyawan melalui Motivasi Kerja Sebagai Variabel Intervening (Studi Kasus pada Karyawan Bagian Produksi PT. Sai Apparel Industries Semarang) - Fansyuri Ilham Mudayana; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2016)
Every company always requires its employees to provide the best contribution in the form of performance enhancement. However, the require is not enough if it is not supported by a performance boosters that provided by the company and employees themselves. The boosters are laborer competence, compensation, and good workplace which all of them will increase work motivation. Therefore, PT Sai Apparel Industries as one of the players in national textile industries, can use the result of this research in order to determine its human resources. Furthermore, that is the best way for winning global textile market.The objective of this research is to measure the influence of competence, compensation, and workplace to employee performance through work motivation. The type of this research is explanatory research.  The population which has been used are entire of PT. Sai Apparel Industries’s employees wihich consisted of 2630 people and its sample amounts 96 respondents which is determined by using slovin formula. The sampling technique which has been used is Purposive Non-probality Sampling also known as the type of collecting sample with particular cases. The tata accumulation used interview technique that is supporeted by questionaire instruments with likert scale. The data was analyzed by using the coefficient of determination test, simple and multiple regression analysis, significance test, and path analysis, as well as trimming process with operating SPSS 20.0 computer software.Based on the results, simultaneously competencies, compensation, and workplace significantly influence employees performance with F-count> F-table (52.087> 2.703). Then in the path analysis, there is the influence of mediation / intervening of work motivation in between competence and compensation to employee performance. However, there is no mediation/intervening influence in relationship between wrokplace to employee performance so that resulted in the trimming process. In a conclusion words, when the employee’s competence, amounts of compensation, and a conducive workplace are improved at high level, then the performance of employees would be better with increasing work motivation.